A multicomponent smoking cessation program for adults with Type 2 Diabetes Mellitus (DiMe-SALUD2 project): A study protocol of a randomized controlled trial - Carla López-Núñez; Sergio Fernández-Artamendi; Desirée Ruiz-Aranda; Davinia María Resurrección; Desirée Navas-Campaña (Contemporary Clinical Trials Communications, 2024)
Background: Tobacco use represents a significant public health burden, being especially harmful for smokers with Type 2 Diabetes Mellitus (T2DM). Effective smoking cessation interventions are required for this vulnerable population. The goal is to describe a study protocol of a randomized controlled trial (RCT) aimed at analyzing the effectiveness and efficiency of a multicomponent smoking cessation intervention for T2DM smokers, including a training protocol on healthy lifestyle habits and self-management of T2DM (DiMe-SALUD2 project). Methods: This RCT will assign participants to: (1) Control Group (n = 30), including a brief psychoeducation advice about smoking cessation; (2) Cognitive-behavioral treatment (CBT) for smoking cessation (n = 30), based on a multicomponent program implemented in group-based sessions over an eight-week period; and (3) CBT plus DiMeSALUD2 protocol (n = 30), which will develop an additional psychoeducational protocol specifically designed to improve healthy lifestyle habits. Participants will be assessed at baseline, post-treatment and several follow-ups (1-, 6- and 12-months). Primary outcomes will include smoking abstinence (24-h point prevalence abstinence at post-treatment and 7-day point prevalence at follow-ups) and smoking continuous abstinence. Secondary outcomes will include treatment retention, changes in smoking patterns and nicotine dependence, as well as the impact on T2DM clinical variables, mental health, and quality of life. Discussion: The DiMeSALUD2 program could assist T2DM smokers in quitting tobacco use and improving their overall quality of life. This project will help incorporating improvements in routine clinical practice with T2DM patients, offering a smoking cessation program adapted to their specific needs. Trial registration: ClinicalTrials.gov. Identifier: NCT05885659. Date of registration: June 2nd, 2023.